Spice plants as a biology learning resource based-education for sustainable development - Ratna Dyah Hartanti; Paidi Paidi; Suyitno Aloysius; Heru Kuswanto; Rifqi Rasis (Institute of Advanced Engineering and Science, 2024)
Studying biology has research topics that are closely related to all the living things around the student and important for them to understand thoroughly. One of the local potentials in the environment around students that can be used as a source of learning biology is spice plants. This research is a qualitative descriptive study. The research aims to describe the spice plants in the Botanical Smartpark, which can be used as learning resources. The result of this research shows that there are 57 species and 27 families of spice plants found at the Botanical Smartpark, Yogyakarta, Indonesia. Spice plant biology objects can be used in biology learning by using project-based learning and socio-scientific issues-based learning models. In addition, this local potential can support education for sustainable development (ESD), through environmental conservation.